Oncogenetic Function and Prognostic Value of DNA Topoisomerase II Alpha in Human Malignances: A Pan-Cancer Analysis - Zhao, Fulai; Chang, Junli; Zhao, Peng; Wang, Wenyi; Sun, Xingyuan; Ma, Xiaoping; Yin, Mengchen; Wang, Yongjun; Yang, Yanping (Frontiers in Genetics, 2022)
Increasing studies have revealed significant associations between TOP2A with oncogenesis and prognosis of human cancers; however, pan-cancer analysis has not been reported. Here, we explored the potential carcinogenic function, the association with clinical outcomes of TOP2A in 33 different human cancers. The results showed that TOP2A was amplified in 31 investigated cancers; TOP2A expression was significantly associated with metastasis of six different cancers, and significantly associated with the survivals of patients in ten different cancers; TOP2A encoded protein was obviously upregulated in five available cancers; phosphorylated TOP2A protein at S1106 was significantly upregulated in all six available cancers. Moreover, TOP2A expression was found to be associated with the cancer-associated immune cell infiltration, including fibroblasts, Tregs and macrophages. In addition, Kyoto encyclopedia of genes and genomes (KEGG) pathway and Gene Ontology (GO) enrichment analyses revealed a most significant association between TOP2A with Wnt signaling pathway, and DNA conformation change. This work provides a comprehensive knowledge of TOP2A in different cancers, including carcinogenic function, prognostic values for metastasis and clinical outcomes.